EMPOWERMENT CIVIL SOCIETY UNTUK MENDUKUNG KEBIJAKAN DAN MIMPI DESA TEMAJUK SEBAGAI DESA WISATA DI BATAS NEGERI - Ihsaniyati, Hanifah; Handono, Setiyo Yuli (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
Community empowerment is vital in the development of society, especially for underdeveloped village and on the border of the country as Temajuk Village. This effort is the empowerment of communities includes not only the individual towards self-reliance. The purpose of this study are 1) to analyze the form of community development activities in accordance with the needs of society (social dynamics) and 2) to identify problems and potential Temajuk Village, sub District Paloh, Sambas Regency, West Kalimantan Province. The approach used in this study was qualitative, which focuses on the data or the observed phenomenon, then produces descriptive data. The results showed 1) Temajuk village has a tourist magnet that is potentially on the beautiful beach of "virgin" for about 26 km and the potential of the social and cultural aspects. However Temajuk Village has a variety of constraints such as the limited ability of the HR (Human Resources) in the attitude and the ability to manage, infrastructure and inadequate infrastructure, and limited access to communication networks. ; 2) The community development activities undertaken by Pokdarwis (Group Travel Environmentally Conscious) together with program Kuliah Kerja Nyata (KKN) and the community were discussions (FGD), stabilization Pokdarwis, training of seafood processing, training promotion (branding) Village Tourism Temajuk, and preparation of supporting resources. It made momentum heading Temajuk Village Tourism Village because the local government began to focus on the policy direction to the village of Tourism to increase social welfare Temajuk Village.